Pengembangan Lembar Kerja Peserta Didik (LKPD) Model Terpadu Tipe Connected Berbasis Pendekatan Saintifik untuk Meningkatkan Hasil Belajar Siswa - Luluk Wahyuning Okfitasari; M V Roesminingsih; Suhanadji Suhanadji (Jurnal Pendidikan dan Pembelajaran Kimia, 2020)
This study aims to produce an Integrated Type of Student Worksheet (LKPD) based on a scientific approach that is feasible to use, practically implemented, and effective to improve social learning outcomes for fourth grade elementary school students with 10 steps, namely (1) Identifying learning objectives (2 ) Conduct learning analysis (3) Analyze student character and learning context (4) Formulate specific learning objectives (5) Develop assessment instruments (6) Develop teaching strategies (7) Develop and select teaching materials (8) Design and develop formative evaluations (9 ) Revising learning (10) Designing and developing summative evaluations. To reveal the feasibility of LKPD, a validation sheet instrument was used on two validators and individual student trials and small groups. To express practicality, the observation sheet of the implementation of learning and student activation is used in field trials. As well as to reveal the effectiveness of the learning assessment sheet instrument used in field trials.